POTENSI ENERGI LISTRIK PADA PABRIK KELAPA SAWIT MELALUI PEMBANGUNAN PLTBG - Stieven N. Rumokoy; Dezetty Monika (Jurnal Poli-Teknologi, 2018)
ABSTRACTPalm oil mills will produce liquid waste which is often called POME (Palm Oil Mill Effluent). This waste if not handled properly will disrupt the environment, even though POME stores a large potential of energy that can be used to support energy needs. With special processing, POME can produce biogas. Then biogas can be used as fuel for generators and ultimately can produce electricity. The process of processing from POME to biogas can be formed in a Biogas Power Plant (PLTBg). The amount of electrical energy that can be generated depends on the amount of biogas formed, while the amount of biogas that will be obtained generally depends on the volume of POME and the content of COD (Chemical Oxigen Demand) in POME. In the sample factory, one year of data has been taken. From the results of the analysis of the prediction of the calculation of electricity energy in palm oil mills through the construction of Biogas Power Plants, the average predicted monthly biogas that can be obtained based on data is 279023,248 Nm3CH4/month and maximum biogas that can be obtained based on the maximum processing of coconut mills oil palm is 506153.34 Nm3CH4/month. The average predictable generating capacity based on data is 1.3 MWe and the maximum capacity that can be built should be around 2.37 MWe.Keywords : Palm Oil Waste, POME, Biogas, Renewable Energy, MetaneABSTRAKPabrik kelapa sawit akan menghasilkan limbah cair yang sering disebut POME (Palm Oil Mill Effluent). Limbah ini jika tidak ditangani dengan baik akan mengganggu lingkungan, padahal POME menyimpan potensi energi yang besar yang dapat dipergunakan untuk mendukung kebutuhan energi. Dengan proses pengolahan khusus, POME dapat menghasilkan biogas. Biogas kemudian dapat dimanfaatkan sebagai bahan bakar untuk genset biogas yang akhirnya dapat menghasilkan listrik. Proses pengolahan dari POME menjadi biogas dapat dibentuk dalam suatu Pembangkit Listrik Tenaga Biogas (PLTBg). Jumlah energi listrik yang dapat dihasilkan bergantung pada jumlah biogas yang terbentuk, sedangkan jumlah biogas yang akan diperoleh pada umumnya bergantung dari volume POME dan kandungan COD (Chemical Oxigen Demand) pada POME. Pada pabrik sampel, data satu tahun telah diambil. Dari hasil analisis prediksi perhitungan pendapatan energi listrik pada pabrik kelapa sawit melalui pembangunan PLTBg, rata-rata prediksi tiap bulan biogas yang dapat diperoleh berdasarkan data adalah 279023.248 Nm3CH4/bulan dan maksimum biogas yang dapat diperoleh berdasarkan maksimum pengolahan pabrik kelapa sawit adalah 506153.34 Nm3CH4/bulan. Rata-rata kapasitas pembangkit yang dapat diprediksi berdasarkan data adalah 1.3 MWe dan maksimum kapasitas yang dapat dibangun sebaiknya sekitar 2.37 MWe.Kata kunci : Limbah, POME, Biogas, Energi Baru dan Terbarukan, Metana